Identitas nasional di era globalisasi: relevansi, transformasi dan strategi penguatan - Pamungkas, Muhammad Nawaf Candra (Maliki Interdisciplinary Journal, 2025)
Globalization brings new challenges and opportunities for strengthening national identity in Indonesia. This article aims to analyze the relevance, transformation, and strategies for strengthening national identity in facing the flow of globalization and the development of digital technology. Using a qualitative descriptive approach based on literature studies, this study examines changes in cultural values, the influence of foreign cultures, and the threat of identity crises, especially in the younger generation. This article discusses various strategies for strengthening national identity, such as character education, preserving local culture, utilizing digital technology, state policies, and empowering the younger generation and local communities. The results of the analysis show that strengthening national identity requires an integrated approach that is able to balance adaptation to global developments with the preservation of indigenous cultural values. In addition, the active role of the younger generation and cross-sector collaboration are the keys to the success of this strategy. This study recommends that the government and society formulate innovative policies and programs that are responsive to global dynamics without ignoring the roots of national culture, so that the nation's identity remains strong and competitive in the global era.